Work above the working time specified in the employment contract in part-time employment - Jaskulska, Jagoda; Rutkowska, Beata (Studia Iuridica Toruniensia, 2023)
This article deals with work above the working time specified in the em- ployment contract in part-time employment. This issue is regulated by Article 151 § 5 of the Labour Code, according to which the parties agree in the employment contract on the permissible number of hours of work in excess of the contractually specified working time of a part-time employee, the exceeding of which entitles the employee, in addition to the normal remuneration, to an overtime bonus. The quoted regulation is not comprehensive and unambiguous, which consequently contributes to inter- pretation disputes, which in turn adversely affect the practice of part-time employment. Therefore, the study proposes amendments to Article 151 § 5 of the Labour Code – on the one hand, to introduce a provision expressly providing that a part-time employee is entitled to an allowance for each hour of work above the working time specified in the employment contract (it will make the right to this allowance completely independent of the will of the parties to the employment relationship), while on the other hand – to impose on the employee and the employer the obligation to determine the maximum number of hours of that work in the employment contract, with the reservation, however, that the absence of a reference to this issue in the contract is tantamount to the admissibility of work above the working time specified in the employment contract up to a full-time position.